2020
DOI: 10.3389/fneur.2020.578924
|View full text |Cite|
|
Sign up to set email alerts
|

Contributing Factors and Evolution of Impulse Control Disorder in the Luxembourg Parkinson Cohort

Abstract: Background: To establish the frequency of impulse control disorder (ICD) in Parkinson's disease (PD).Methods: Within the Luxembourg Parkinson's Study, PD patients were evaluated for ICD presence (score ≥ 1 on MDS-UPDRS I item 1.6), use of dopamine agonists (DA) and other medications.Results: 470 patients were enrolled. Among 217 patients without DA use, 6.9% scored positive for ICD, vs. 15.4% among 253 patients with DA use (p = 0.005). The regression analysis showed that age at PD diagnosis had only a minor im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Dopaminergic preparations are most effective and play a central role in modern Parkinson therapies, as evident from international evidence-based guidelines [1][2][3][4]. Most of these guidelines list both dopamine agonists and levodopa as possible first-choice drugs, but there is an increasing concern about adverse effects of dopamine agonists, especially impulse control disorders (ICDs) [5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dopaminergic preparations are most effective and play a central role in modern Parkinson therapies, as evident from international evidence-based guidelines [1][2][3][4]. Most of these guidelines list both dopamine agonists and levodopa as possible first-choice drugs, but there is an increasing concern about adverse effects of dopamine agonists, especially impulse control disorders (ICDs) [5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…It has been known for many years that dopamine replacement therapy in PD may cause ICDs such as hypersexuality and pathological gambling [13][14][15][16], but more recent studies have shown that ICDs are most common in patients using dopamine agonists [5][6][7][8][9][10][11][12][17][18][19]. Gambling, compulsive sexual behavior, compulsive shopping and binge-eating are defined as ICDs, but many patients also experience other symptoms related to reduced impulse control, such as punding, hobbyism and dopamine dysregulation syndrome [20].…”
Section: Introductionmentioning
confidence: 99%